Performance analysis on series and parallel circuit configurations of a four-cell thermoelectric generator module design / Muhammad Hadrami Hamdan ... [et al.] - Hamdan, Muhammad Hadrami; Mat Som, Nur Aqilah; Abdul Rashid, Amirul; Jimmy, Gilbert Jugi (Smart Manufacturing Research Institute (SMRI), 2021)
This study presents a technique in recovering energy from low-grade waste heat of a Proton Exchange Membrane Fuel Cell (PEMFC). The goal is to study the functionality and performance using a multiple cell thermoelectric generator (TEG) module. The test bench consists of a heating element, a test section, and a cooling section. The heating element supplies a hot stream temperature of 53°C and 58°C that represents the waste heat from an actual PEMFC stack. The module comprises four TEG cells with heat pipes coupled with a heat sink system. The main variables were the TEG cooling modes of natural convection (0 m/s) and forced convection (at 5 m/s and 10 m/s) and the series and parallel circuit configurations of the module. At 58°C waste heat temperature, forced convection cooling at 10 m/s gave the highest voltage and power output of 140 mV and 1960 µW. The outputs of the series circuit was 159% higher than the parallel circuit. This initial simple TEG module design has shown that it has a good prospect to compensate for the ultra-low waste heat temperature of a PEMFC. Future designs of the modules need to identify a more optimized approach to improve the outputs and contribute to the long-term sustainability of PEMFC systems.